Women, Personhood, and the Male God: A Feminist Critique of Patriarchal Concepts of God in View of Domestic Abuse. (September 2019) - Moder, Ally
Domestic abuse is a common occurrence for women in the Christian Church. Underlying this dark reality is a long history of patriarchal theological interpretations that have depicted God as a dominant male figure that subjects women to male hierarchy as a subordinate. Often based on an understanding of Jesus as subordinate to God the Father in the Trinity, the correlated praxis of the Church has commonly been to subject women to suffering at the hands of men – even at the cost of their lives – thus mimicking the death of Christ. This deeply flawed androcentric theology and subsequent praxis of women's subordination has been severely challenged by liberal feminists, and rightly so for the sake of women's survival and flourishing. This article utilizes the Social Trinity to provide a Christian feminist critique of patriarchal atonement models and theology towards the feminist goal of liberating women from male-perpetrated violence. Ultimately a reframing of God will be presented that includes women as full persons and calls them to resist the suffering of domestic abuse and to reclaim their full personhood as the imago Dei .